Lack of association between pseudoexfoliation syndrome and manganese superoxide dismutase polymorphism - Yuce, Huseyin; Hepsen, Ibrahim F.; Tekederei, Ibrahim; Keskin, Ugurcan; Elyas, Halit; Akyol, Omer (Taylor & Francis Inc, 2007)
Purpose: The aim of this clinical study was to investigate the possible association between manganese superoxide dismutase (Mn-SOD) enzyme polymorphism in the mitochondrial targeting sequence and pseudoexfoliation syndrome. Methods: Ala (GTT) or Val (GCT) polymorphism in the signal peptide of Mn-SOD gene was evaluated using a primer pair to amplify a 107-bp fragment followed by digestion with restriction enzyme NgoM IV. Results: The frequencies of Ala-9 and Val-9 variants and genotypes of Mn-SOD were similar in the controls and pseudoexfoliation syndrome patients. Conclusions: These results suggest no major modifying role for the Mn-SOD gene polymorphism in patients with pseudoexfoliation syndrome.
Keywords: manganese superoxide dismutase; polymorphism; pseudoexfoliation syndrome